The Mediating Effects of Board Role Performance in the Relationship Between Board Capital and Survival of Financial Cooperatives in Uganda - Francis Yosa; Colin Agabalinda; Alain Vilard Isoh (SEISENSE Business Review)
Savings and Credit Cooperative Societies (SACCOs) in Uganda face persistent survival challenges, often associated with governance limitations and board effectiveness issues. This study investigates the association between board capital, which encompasses both human and social capital, and SACCO survival—measured through liquidity and gearing—with board role performance as a potential mediator. Data were collected from 311 participants across 60 SACCOs in a cross-sectional survey. Structural equation modeling analysis indicates that although board capital does not directly influence SACCO survival, it positively correlates with board role performance, which in turn is significantly associated with SACCO survival outcomes of liquidity and gearing. These findings underscore the importance of board engagement in translating board members’ collective expertise, knowledge, and external connections into enhanced liquidity and balanced gearing for SACCOs. Practical implications suggest that SACCOs could benefit from initiatives to strengthen board members' skills and networking capabilities through targeted training, mentorship, and structured networking opportunities. Establishing clear board roles, strengthening accountability mechanisms, and implementing regular performance evaluations are essential practices to bolster SACCO survival. This study contributes a novel perspective by integrating Role Theory with Agency and Resource Dependency Theories, providing a multi-theoretical framework to better understand SACCO survival in a developing economy context. This integration enriches the theoretical landscape and provides actionable insights for strengthening SACCO survival in Uganda’s challenging economic context.